2011
DOI: 10.1155/2011/854651
|View full text |Cite
|
Sign up to set email alerts
|

Patella Eversion Reduces Early Knee Range of Motion and Muscle Torque Recovery after Total Knee Arthroplasty: Comparison between Minimally Invasive Total Knee Arthroplasty and Conventional Total Knee Arthroplasty

Abstract: We hypothesized that patella eversion during total knee arthroplasty (TKA) reduces early return of active knee extension and flexion, quadriceps muscle strength, and postoperative pain. In 100 conventional TKA knees and 100 minimally invasive TKA (MIS TKA) knees, we compared knee range of motion (ROM), postoperative pain, and quadriceps muscle strength at 1 day, 4 days, 1 week, 2 weeks, 3 weeks, 4 weeks, 12 weeks, 1 year, and 5 years after surgery. The differences of surgical approach between MIS TKA and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 23 publications
(19 reference statements)
3
32
1
Order By: Relevance
“…Many authors assessed quadriceps function in terms of rehabilitation milestones (eg, straight leg raise) after MIS and standard TKAs [8,16,20,25,33]. The findings in those studies are consistent, in that quadriceps function was superior with a MIS TKA during the first postoperative week [8,16,33].…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Many authors assessed quadriceps function in terms of rehabilitation milestones (eg, straight leg raise) after MIS and standard TKAs [8,16,20,25,33]. The findings in those studies are consistent, in that quadriceps function was superior with a MIS TKA during the first postoperative week [8,16,33].…”
Section: Introductionmentioning
confidence: 96%
“…Many authors assessed quadriceps function in terms of rehabilitation milestones (eg, straight leg raise) after MIS and standard TKAs [8,16,20,25,33]. The findings in those studies are consistent, in that quadriceps function was superior with a MIS TKA during the first postoperative week [8,16,33]. Only a few studies reported on quadriceps function in terms of rehabilitation milestones beyond the first postoperative week; Kolisek et al [25] reported no strength differences 12 weeks after surgery, and the strength findings observed by Karpman and Smith [20] 2 weeks postoperative were dependent on the type of MIS approach (quadriceps-sparing superior, but mini-midvastus not superior as compared with medial parapatellar).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations